TINJAUAN TERHADAP TINDAK PIDANA PENCURIANDENGAN KEKERASAN DI KABUPATEN KUTAI KARTANEGARA - Merida Kristin (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Crime of theft with violence is contained in the second book of the Criminal Code Article 365. Theft by violence is theft with qualifications and is also a theft with incriminating elements. The form of criminal liability imposed on the perpetrators of criminal offenses accompanied by violence is contained in Article 365 of the Criminal Code. The article generally regulates the form of accountability for robbery accompanied by violence, but for the regulation of the form of accountability for robbery accompanied by more specific violence, it is regulated in Article 365 paragraph 2, then the form of accountability for perpetrators of robbery accompanied with imprisonment sentenced to prison with imprisonment for 12 (twelve) years. Furthermore, the violence intended here is an act that uses body energy that is not light. Bodily energy is physical strength directed at humans and not violence against goods. Crime of theft by violence arises due to several factors, both those related to the perpetrators and the victims and the environment in which they live and interact. Based on the background above, the authors are interested in choosing a title with the theme "Review of Crime of Theft with Violence in Kutai Kartanegara Regency". And in this study using empirical sociological research methods. It is expected that from the results of this thesis writing research can contribute ideas related to the issues raisedKeywords : Theft, Crime and Violence.